Exosomes Derived from Mesenchymal Stem Cells Ameliorate Hypoxia/Reoxygenation-Injured ECs via Transferring MicroRNA-126 - Qunwen Pan; Yan Wang; Qing Lan; Weiquan Wu; Zhenxuan Li; Xiaotang Ma; Liming Yu (Hindawi Limited, 2019)
Mesenchymal stem cells (MSCs) show protective effects on ischemia/reperfusion- (I/R-) induced endothelial cell (EC) injury and vascular damage. Stem cell-released exosomes (EXs) could modulate target cell functions by delivering their cargos, and exert therapeutic effects as their mother cells. miR-126 is an important regulator of EC functions and angiogenesis. In this study, we determined whether EXs released from MSC-EXs provided beneficial effects on hypoxia/reoxygenation- (H/R-) injured ECs by transferring miR-126. MSCs were transfected with a miR-126 mimic or miR-126 short hairpin RNA to obtain miR-126-overexpressing MSC-EXs (MSC-EXsmiR-126) and miR-126 knockdown MSC-EXs (MSC-EXsSimiR-126). For functional studies, H/R-injured ECs were coincubated with various MSC-EXs. The viability, migration, tube formation ability, and apoptosis of ECs were measured. miR-126 and proangiogenic/growth factor (VEGF, EGF, PDGF, and bFGF) expressions were detected by qRT-PCR. Akt, p-Akt, p-eNOS, and cleaved caspase-3 expressions were examined by western blot. The PI3K inhibitor (LY294002) was used in pathway analysis. We found that overexpression/knockdown of miR-126 increased/decreased the proliferation of MSCs, as well as miR-126 expression in their derived MSC-EXs. MSC-EXsmiR-126 were more effective in promoting proliferation, migration, and tube formation ability of H/R-injured ECs than MSC-EXs. These effects were associated with the increase in p-Akt/Akt and p-eNOS, which could be abolished by LY294002. Besides, MSC-EXsmiR-126 were more effective than MSC-EXs in reducing the apoptosis of ECs, coupled with the decrease in cleaved caspase-3. Moreover, compared to MSC-EXs, MSC-EXsmiR-126 significantly upregulated the level of VEGF, EGF, PDGF, and bFGF in H/R-injured ECs. Downregulation of miR-126 in MSC-EXs inhibited these effects of MSC-EXs. The results suggest that MSC-EXs could enhance the survival and angiogenic function of H/R-injured ECs via delivering miR-126 to ECs and subsequently activate the PI3K/Akt/eNOS pathway, decrease cleaved caspase-3 expression, and increase angiogenic and growth factors.